Blocking NMDA-Receptors in the Pigeon’s Medial Striatum Impairs Extinction Acquisition and Induces a Motoric Disinhibition in an Appetitive Classical Conditioning Paradigm - Gao, Meng; Pusch, Roland; Güntürkün, Onur (Frontiers in Behavioral Neuroscience, 2019)
To uncover the variant and invariant neural properties of extinction learning, we use pigeons as an animal model in an appetitive extinction paradigm. The dorsal striatum of mammals plays a key role in the extinction of learned behavior. Since the medial striatum of birds resembles the mammalian dorsal striatum, we here targeted a medial sub-region of the pigeon’s striatum that receives executive, visual and motor pallial projections. By locally antagonizing the N-methyl-D-aspartate (NMDA) receptors through 2-Amino-5-phosphonovalerianacid (APV) during extinction, we observed an impairment of extinction acquisition and a disinhibition of the conditioned pecking to reward stimuli. Based on various evidences, we assume that the delayed extinction effect is caused by deficits in the updating of value coding of altered reward contingencies. It is likely that this deficit results at least in part from an insufficient integration of input from the avian prefrontal-like area, that transmits information on reward amount and subjective reward value. We further assume that APV-induced increase of pecking to rewarded cues results from local hyperactivity patterns that primarily drives operant actions towards targets of high appetitive value. The overall correspondence of our results with those from mammals suggests common neural substrates of extinction and highlights the shared functionality of the avian and mammalian dorsal striatum despite 300 million years of independent evolution.